Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3349/ymj.2018.59.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Unenhanced Computed Tomography with Iterative Reconstruction for Diagnosis of Ureter Stones

Abstract: PurposeTo study the clinical application of low-dose unenhanced computed tomography with iterative reconstruction technique (LDCT-IR) on renal colic in the emergency department.Materials and MethodsWe conducted a prospective, single-blinded, randomized, and non-inferiority study. From March 2014 to August 2015, 112 patients with renal colic were included, and were randomized to either LDCT-IR (n=46) or standard-dose unenhanced CT (SDCT) (n=66) groups. The accuracy of urolithiasis diagnosis was the primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Dual energy XCT is often used with contrast agents which include elements such as iodine and barium, although non-contrast scans are current practice as well. [16] Elements with K edges in the range of medical x-rays would likely require one or more additional tube voltages, or a scan with a limited spectral range, to provide a complete picture of the patient or sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual energy XCT is often used with contrast agents which include elements such as iodine and barium, although non-contrast scans are current practice as well. [16] Elements with K edges in the range of medical x-rays would likely require one or more additional tube voltages, or a scan with a limited spectral range, to provide a complete picture of the patient or sample.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lalonde and Bouchard [9] suggested that two tube voltages were required for soft tissue and an additional two tube voltages could be used for bony tissue, leading to a suggestion that measurements at three or four tube voltages would have an advanges over dual energy XCT for natural (i.e., not contrast enhanced) tissue. [16] Here, we will differ somewhat from previous studies in looking directly at the the intrinsic dimensionality of the Hounsfield unit measurements as a function of tube voltage instead of considering the intrinsic dimensionality of the x-ray cross sections themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Taking all the 17 studies into consideration, the sensitivity estimates ranged from 0.70 to 0.98 and the speci city estimates ranged from 0.39 to 1.00. The result of heterogeneity test showed that 3 studies [20,26,30] have obvious heterogeneity (Supplemental Fig. 4).…”
Section: Data Extraction and Meta-analysismentioning
confidence: 99%
“…full-text articles were later excluded due to these reasons: retrospective studies (n = 4), without speci c number of TP, FP, FN, TN(n = 3), without effective dose (n = 1). Finally, A total of 17 unique articles with 1,761 patients (mean age: 46.40) and 2,053 stones were included [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] for the quantitative analysis. 13 studies [14][15][16][17][18][19][20][21][22][23][24][25][26] were included in the former studies [10][11], and 4 studies [27][28][29][30] were new studies.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Given that non-contrast computed tomography (NCCT) has become the gold standard of diagnosing urinary stones [10,11], many groups have focused on the relation between Hounsfield units (HU), especially mean stone density (MSD), and urinary stone composition or treatment outcome [12]. In addition to MSD, the stone heterogeneity index (SHI), also known as standard deviation of HU, and the variant coefficient of stone density (VCSD) have emerged as potential therapeutic gauges [13,14].…”
Section: Introductionmentioning
confidence: 99%